2022
DOI: 10.1021/acsphotonics.2c00289
|View full text |Cite
|
Sign up to set email alerts
|

Microcavity-Modified Emission from Rare-Earth Ion-Based Molecular Complexes

Abstract: Despite the remarkable optical properties of rare-earth ion materials, their applications as light sources and in quantum technologies are often hindered by their long lifetimes and weak emission.Leveraging the natural compatibility of rare-earth ion molecular complexes with photonic structures, here we modify their photoluminescence properties by coupling them to a flexible open Fabry-Pérot cavity. The full in situ tunability of the Fabry-Pérot cavity allows fine control over its cavity modes and the achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…[10,11] Such rare-earth coordination complexes are also uniquely advantageous in developing rational blueprints for the design and synthesis of new structures with improved functions for potential applications. [12,13] However, the role of counterions and the formation of rare-earth complex clusters have yet to be explored at the single complex level. Recently, it has been demonstrated that by efficient protection of the surrounding ligands, the rare-earth ions in the complexes together with counterions can remain charged even on a metallic surface.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Such rare-earth coordination complexes are also uniquely advantageous in developing rational blueprints for the design and synthesis of new structures with improved functions for potential applications. [12,13] However, the role of counterions and the formation of rare-earth complex clusters have yet to be explored at the single complex level. Recently, it has been demonstrated that by efficient protection of the surrounding ligands, the rare-earth ions in the complexes together with counterions can remain charged even on a metallic surface.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, cavity (polariton) chemistry has become an active field due to its potential applications in the alteration of chemical kinetics, the modification of electron transfer, the realization of polariton-mediated intermolecular energy transfer, and the enhancement of spontaneous emission rates. In this research area, the collective effect of a group of molecules interacting with confined electromagnetic fields has received extensive attention because this effect is viewed as the origin of polariton formations. Superradiance is a kind of collective effect and has been widely studied since the pioneering work done by Dicke . Recently, several experimental studies pertinent to superradiance in cavities have been realized, and some of the results can be explained by the Tavis–Cummings (TC) model, , which provides an exact solution for N molecules coupled to a single photonic mode .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate that X-ray spectroscopy at atomic limits can be performed at room temperature. This work also provides a fundamental understanding of rare-earth ions coordinated with the molecules and will be useful for designing novel rare-earth molecular systems. , …”
Section: Introductionmentioning
confidence: 99%